2015
DOI: 10.3109/03630269.2015.1039026
|View full text |Cite
|
Sign up to set email alerts
|

Compound Heterozygosity for HKααand anin CisDeletion of DoubleαGenes Presents asα-Thalassemia Trait

Abstract: The HKαα (Hong Kongαα) allele is an unusual rearrangement of the α-globin gene cluster containing both the -α(3.7) (rightward) and ααα(anti 4.2) crossover deletion/insertion. During our thalassemia screening program, we identified 10 adult individuals and two newborns who were confirmed to be compound heterozygotes for HKαα and the Southeast Asian deletion (- -(SEA)). Their hematological data showed a typical α-thalassemia (α-thal) trait. The routine gap-polymerase chain reaction (gap-PCR) based assay revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…This allele contains an intact a2 gene and a a1-a2 fusion gene (-a 3.7 ) with neither decreased nor enhanced aglobin gene dosage. We have confirmed that compound heterozygosity for HKaa and an in cis deletion of double a genes presents as a-thalassemia trait [11]. It can also be speculated that carriers of b-thalassemia trait are unlikely to suffer any more deteriorative effects when combined with the HKaa allele since its imbalanced a/b ratio is unchanged.…”
supporting
confidence: 75%
“…This allele contains an intact a2 gene and a a1-a2 fusion gene (-a 3.7 ) with neither decreased nor enhanced aglobin gene dosage. We have confirmed that compound heterozygosity for HKaa and an in cis deletion of double a genes presents as a-thalassemia trait [11]. It can also be speculated that carriers of b-thalassemia trait are unlikely to suffer any more deteriorative effects when combined with the HKaa allele since its imbalanced a/b ratio is unchanged.…”
supporting
confidence: 75%
“…As shown in Figure 3 , Integrative Genomics Viewer plots of HKαα allele reveal that there is virtually no deletion or duplication of the gene. Therefore, individuals with HKαα/αα presented a normal hematological phenotype, and this structural variant does not aggravate the clinical phenotype of patients even when combined with other α/β-mutations, which is consistent with previously reported results ( 7 , 8 , 11 , 19 , 21 ). Although the carrier rate of the HKαα allele is low and the carriers do not have any clinical manifestations, its molecular diagnosis has important clinical significance.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have reported that individuals with the HKαα allele present with normal hematological phenotype (8)(9)(10). Individuals with compound heterozygote of HKαα and --SEA showed a typical α-thalassemia trait (11). Although the HKαα allele does not have any deleterious effect on the clinical phenotype of carriers, genetic testing of the HKαα allele has important implications for genetic counseling and prenatal diagnosis.…”
Section: Original Articlementioning
confidence: 99%